Características maternas del Near Miss y sus causas - Ramos Becerra, Ronald Jefferson (Machala : Universidad Técnica de Machala, 2021)
It is considered Near Miss Maternal, when a pregnant woman is about to die and survives a complication that could have affected her integrity, due to timely medical intervention or luck, up to 42 days after delivery. Objective: to determine the maternal characteristics and the causes of extreme maternal morbidity (near miss), through the review and analysis of scientific articles to provide better care for pregnant women in primary health care. Methodology: Bibliographic review, analytical synthetic method, by searching scientific articles, since 2017, using data platforms such as: PUBMED, MEDSCAPE, COCHRANE, GOOGLE SCHOLAR. Conclusions: The characteristics of the mothers who present Near Miss are: age between 19 to 35 years, incomplete secondary studies, multiparous women, history of abortions, with full-term pregnancy, prenatal controls of less than 4 years and having undergone cesarean sections, These data should be taken into account at the time of care for pregnant women in order to provide adequate obstetric care. The main causes of maternal near misses are: Hypertensive Disorders of Pregnancy and Postpartum Hemorrhages, spontaneous abortion and ectopic pregnancy.
Se considera Near Miss Maternal, cuando una gestante está a punto de morir y sobrevive a una complicación que podría haber afectado su integridad, debido a la intervención médica oportuna o suerte, hasta los 42 días luego del parto. Objetivo: determinar las características maternas y las causas de morbilidad extrema materna (near miss), mediante la revisión y análisis de artículos científicos para brindar una mejor atención a las gestantes en la atención primaria de salud. Metodología: Revisión bibliográfica, método sintético analítico, mediante la búsqueda de artículos científicos, desde el año 2017, utilizando plataformas de datos como: PUBMED, MEDSCAPE, COCHRANE, GOOGLE SCHOLAR. Conclusiones: Las características de las maternas que presentan Near Miss, son: edad entre los 19 a 35 años, estudios secundarios incompletos, mujeres multíparas, antecedentes de abortos, con embarazo a término, controles prenatales menores a 4 y haber sido sometida a cesáreas, debiéndose tener en cuenta estos datos, en el momento de la atención a las gestantes a fin de dar una adecuada atención obstétrica. Las causas principales de cuasi accidentes maternos, son: Los Trastornos Hipertensivos del Embarazo y Hemorragias postparto, aborto espontáneo y embarazo ectópico.
Keywords: MORBILIDAD MATERNA EXTREMA; NEAR MISS MATERNAL; CUASI ACCIDENTE MATERNO; CARACTERISTICAS